2019
DOI: 10.2135/cropsci2018.09.0573
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative Disease Resistance Loci towards Phytophthora sojae and Three Species of Pythium in Six Soybean Nested Association Mapping Populations

Abstract: Comparison of quantitative disease resistance loci (QDRL) towards the diverse array of soilborne pathogens that affect soybean [Glycine max (L.) Merr.] is key to the incorporation of resistance in breeding programs. The water molds Phytophthora sojae (Kauffman & Gerdmann), Pythium irregulare (Buisman), Pythium ultimum var. ultimum (Trow), and Pythium ultimum var. sporangiiferum (Drechsler) contribute to soybean yield losses annually. Six Soybean Nested Association Mapping (SoyNAM) populations were evaluated fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
36
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 28 publications
(40 citation statements)
references
References 82 publications
3
36
0
Order By: Relevance
“…The QDRL for P. irregulare in POP3 on chromosome 1 was in the same chromosomal region as a QDRL found for the same species by Scott et al (2019) in the NAM population of IA3023 × LG00-3372. The QDRL in the NAM population was found for the adjusted root weight trait and explained 6.9% of the variation.…”
Section: Discussionsupporting
confidence: 74%
See 3 more Smart Citations
“…The QDRL for P. irregulare in POP3 on chromosome 1 was in the same chromosomal region as a QDRL found for the same species by Scott et al (2019) in the NAM population of IA3023 × LG00-3372. The QDRL in the NAM population was found for the adjusted root weight trait and explained 6.9% of the variation.…”
Section: Discussionsupporting
confidence: 74%
“…Several studies have measured resistance toward different Pythium species ( Rod et al, 2018 ; Lerch-Olson et al, 2020 ) and have identified QDRL, mostly minor, in RIL populations of soybean ( Ellis et al, 2013 ; Stasko et al, 2016 ; Urrea et al, 2017 ; Klepadlo et al, 2019 ; Lin et al, 2018 , 2020 ; Scott et al, 2019 ). Almost all of the studies have shown partial resistance aside from one study by Rosso et al (2008) showing monogenic resistance.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Thus, studies to map the genetic positions of QDR can be applied to increase the efficiency of selection for these traits via MAS [41].Numerous biparental mapping studies identified QDR loci (QDRL) towards P. sojae in US cultivars Conrad, Sloan,. Recently, the soybean nested associated mapping populations were used to study P. sojae resistance, identifying four QDRL [49]. In addition to US cultivars, QDRL have been mapped in landraces originating from China and the Republic of Korea (South Korea, SK) using biparental mapping populations derived from crosses with eight accessions [50][51][52][53][54].…”
mentioning
confidence: 99%